A computational algorithm for calculating the effect of the electromagnetic fields to thin complex configured plates - Nuraliev, Fakhriddin; Safarov, Shohruh; Artikbayev, Mahkam (2020 International Conference on Information Science and Communications Technologies (ICISCT), 2020)
A nonlinear mathematical model of a flexible magneto-elastic plate (in motion subject to forces) is developed on the Lagrange principle. A computational algorithm is presented to estimate the geometry of magnetic plates. The algorithm is based on R-Function and Galerkin methods. These methods are used to develop a computational scheme. The cases of simple and complex structures of magneto-elastic flexible plates are considered and solutions are obtained under specific boundary conditions. These conditions are defined with some concrete requirements of engineering.